Crystallographic-shear-phase-driven W18O49 nanowires growth on nanocrystalline W surfaces. (1st April 2016) - Srivastav, Ajeet K.; Basu, Joysurya; Kashyap, Sanjay; Chawake, Niraj; Yadav, Devinder; Murty, B.S.
Abstract: The present paper reports the growth and branching mechanism of W18 O49 nanowires grown on nanocrystalline tungsten (W) surfaces. Nanocrystalline W powder was prepared using high energy ball milling. The nanopowder was non-isothermally heat-treated up to 1400 °C in argon atmosphere. The nanowires of 30–50 nm diameter were observed on nanopowder surfaces after the heat-treatment. A model based on crystallographic shear phase formation to accommodate the oxygen deficiency during the reduction of WO3 is discussed to explain the growth and branching mechanism of these nanowires which correlates well with the observed angle for the branching. Graphical abstract: